2021
DOI: 10.3389/fimmu.2021.652782
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 3 Inhibits Acetaminophen-Induced Liver Pyroptosis Through the Regulation of Mitochondrial ROS

Abstract: Pyroptosis is a newly discovered form of cell death. Peroxiredoxin 3 (PRX3) plays a crucial role in scavenging reactive oxygen species (ROS), but its hepatoprotective capacity in acetaminophen (APAP)-induced liver disease remains unclear. The aim of this study was to assess the role of PRX3 in the regulation of pyroptosis during APAP-mediated hepatotoxicity. We demonstrated that pyroptosis occurs in APAP-induced liver injury accompanied by intense oxidative stress and inflammation, and liver specific PRX3 sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 58 publications
(86 reference statements)
2
47
0
Order By: Relevance
“…Prxs are well-known antioxidant proteins that scavenge peroxides in cells. In this aspect, many studies demonstrated that Prxs could play a protective role in diverse disease models ( 24 25 26 27 28 ). Recent evidence has suggested that Prxs could possibly act as DAMP molecules mediating the secretion of inflammatory cytokines as shown in various disease models ( 1 6 7 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prxs are well-known antioxidant proteins that scavenge peroxides in cells. In this aspect, many studies demonstrated that Prxs could play a protective role in diverse disease models ( 24 25 26 27 28 ). Recent evidence has suggested that Prxs could possibly act as DAMP molecules mediating the secretion of inflammatory cytokines as shown in various disease models ( 1 6 7 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The excessive amounts of glutathione needed to eliminate toxic NAPQI results in oxidative stress in cells, which finally leads to mitochondrial dysfunction, inflammasome activation, and cell death through apoptosis as well as pyroptosis [ 89 ]. Wang, et al studied animal models of drug-induced acute liver injury caused by the intraperitoneal administration of APAP or carbon tetrachloride, and found the processing of GSDMD into its p30 pore forming fragment, procaspase-1 into its p20 active fragment, and pro-IL-1ÎČ into its mature form, suggesting inflammasome-dependent pyroptosis in APAP-induced acute liver injury [ 90 ]. The activation of inflammasome-dependent pyroptosis by APAP was also observed in primary cultures of hepatocytes as well as Kupffer cells, indicating that both liver parenchymal cells and immune cells contribute to acute liver injury [ 90 ].…”
Section: Prdxsmentioning
confidence: 99%
“…Wang, et al studied animal models of drug-induced acute liver injury caused by the intraperitoneal administration of APAP or carbon tetrachloride, and found the processing of GSDMD into its p30 pore forming fragment, procaspase-1 into its p20 active fragment, and pro-IL-1ÎČ into its mature form, suggesting inflammasome-dependent pyroptosis in APAP-induced acute liver injury [ 90 ]. The activation of inflammasome-dependent pyroptosis by APAP was also observed in primary cultures of hepatocytes as well as Kupffer cells, indicating that both liver parenchymal cells and immune cells contribute to acute liver injury [ 90 ]. They also demonstrated that APAP-induced liver pyroptosis could be ameliorated and reduced by the siRNAs for NLRP3 and Prdx3, showing that liver injury by APAP is dependent on NLRP3 inflammasomes and negatively regulated by Prdx3 [ 90 ].…”
Section: Prdxsmentioning
confidence: 99%
See 2 more Smart Citations